A general framework for propagule dispersal in mangroves. (6th May 2019) - Van der Stocken, Tom; Wee, Alison K. S.; De Ryck, Dennis J. R.; Vanschoenwinkel, Bram; Friess, Daniel A.; Dahdouh‐Guebas, Farid; Simard, Marc; Koedam, Nico; Webb, Edward L.
ABSTRACT: Dispersal allows species to shift their distributions in response to changing climate conditions. As a result, dispersal is considered a key process contributing to a species' long‐term persistence. For many passive dispersers, fluid dynamics of wind and water fuel these movements and different species have developed remarkable adaptations for utilizing this energy to reach and colonize suitable habitats. The seafaring propagules (fruits and seeds) of mangroves represent an excellent example of such passive dispersal. Mangroves are halophytic woody plants that grow in the intertidal zones along tropical and subtropical shorelines and produce hydrochorous propagules with high dispersal potential. This results in exceptionally large coastal ranges across vast expanses of ocean and allows species to shift geographically and track the conditions to which they are adapted. This is particularly relevant given the challenges presented by rapid sea‐level rise, higher frequency and intensity of storms, and changes in regional precipitation and temperature regimes. However, despite its importance, the underlying drivers of mangrove dispersal have typically been studied in isolation, and a conceptual synthesis of mangrove oceanic dispersal across spatial scales is lacking. Here, we review current knowledge on mangrove propagule dispersal across the various stages of the dispersal process. Using a general framework, we outline the mechanisms and ecological processes that are known to modulate the spatial patterns of mangrove dispersal. We show that important dispersal factors remain understudied and that adequate empirical data on the determinants of dispersal are missing for most mangrove species. This review particularly aims to provide a baseline for developing future research agendas and field campaigns, filling current knowledge gaps and increasing our understanding of the processes that shape global mangrove distributions.